THEORETICAL FOUNDATIONS OF FOOD SAFETY MANAGEMENT RESEARCH - Yazina, V. A.; Vyshnikina, O. V.; Sabirov, O. V.; Haponenko, S. O.; Hurbych, N. O. (Systems and Technologies, 2023)
The article is devoted to the study of food safety management at restaurant enterprises. Improving food safety management at restaurant enterprises involves the use of the latest technologies and standards, as well as taking into account legislative requirements in the field of food safety. The enterprise must have appropriate procedures and instructions for the organization of food quality and safety control, as well as ensuring hygiene in the kitchen and in the restaurant. It is also important to ensure that food safety personnel are properly trained and educated so that they can apply procedures and standards correctly. In addition, the company must use high-quality and verified food suppliers. The concept of food safety was considered and its structural elements were determined. The basic principles of food safety management at restaurant enterprises were established. Relevant modern international organizations, their activities and the importance of influence on food safety are analyzed. The main documents at the state level responsible for regulating food safety have been identified. The main incidents of food safety violations and ways to eliminate them are considered. The relevance of the problem of improving food safety management at restaurant enterprises has been proven. The key problems in the field of food safety at restaurant enterprises were studied and the prospects for the development of food safety at restaurant enterprises were determined. Recommendations for improving food safety management at restaurant enterprises have been developed. Improving food safety management at restaurant enterprises is an important element of ensuring the restaurant's competitiveness and reputation. Customers will be more inclined to choose restaurants that maintain high standards of food quality and safety. The research is relevant in modern conditions, as food safety is becoming an increasingly important problem in the restaurant industry. The global COVID-19 pandemic has exacerbated this problem as people have become more aware of hygiene standards in public places, including restaurants. Ensuring food safety at restaurant enterprises is important not only for the health and safety of customers, but also for the successful operation of the enterprise itself. A restaurant's reputation can be seriously damaged if problems with food quality or safety are discovered.